Resprouters Versus Reseeders: Are Wild Rooibos Ecotypes Genetically Distinct? - Brooks, J.; Makunga, N. P.; Hull, K. L.; Brink-Hull, M.; Malgas, R.; Roodt-Wilding, R. (Frontiers in Genetics, 2021)
Aspalathus linearis (Burm. F.) R. Dahlgren (Fabaceae) or rooibos, is a strict endemic species, limited to areas of the Cederberg (Western Cape) and the southern Bokkeveld plateau (Northern Cape) in the greater Cape Floristic Region (CFR) of South Africa. Wild rooibos, unlike the cultivated type, is variable in morphology, biochemistry, ecology and genetics, and these ecotypes are broadly distinguished into two main groups, namely, reseeders and resprouters, based on their fire-survival strategy. No previous assessment of genetic diversity or population structure using microsatellite markers has been conducted in A. linearis. This study aimed to test the hypothesis that wild rooibos ecotypes are distinct in genetic variability and that the ecotypes found in the Northern Cape are differentiated from those in the Cederberg that may be linked to a fire-survival strategy as well as distinct morphological and phytochemical differences. A phylogeographical and population genetic analyses of both chloroplast (trnLF intergenic region) and newly developed species-specific nuclear markers (microsatellites) was performed on six geographically representative wild rooibos populations. From the diversity indices, it was evident that the wild rooibos populations have low-to-moderate genetic diversity (He: 0.618–0.723; Ho: 0.528–0.704). The Jamaka population (Cederberg, Western Cape) had the lowest haplotype diversity (H = 0.286), and the lowest nucleotide diversity (π = 0.006) even though the data revealed large variations in haplotype diversity (h = 0.286–0.900) and nucleotide diversity (π = 0.006–0.025) between populations and amongst regions where wild rooibos populations are found. Our data suggests that populations of rooibos become less diverse from the Melkkraal population (Suid Bokkeveld, Northern Cape) down towards the Cederberg (Western Cape) populations, possibly indicative of clinal variation. The largest genetic differentiation was between Heuningvlei (Cederberg, Western Cape) and Jamaka (FST = 0.101) localities within the Cederberg mountainous region, and, Blomfontein (Northern Cape) and Jamaka (Cederberg) (FST = 0.101). There was also a significant isolation by distance (R2 = 0.296, p = 0.044). The presence of three main clusters is also clearly reflected in the discriminant analysis of principal components (DAPC) based on the microsatellite marker analyses. The correct and appropriate management of wild genetic resources of the species is urgently needed, considering that the wild Cederberg populations are genetically distinct from the wild Northern Cape plants and are delineated in accordance with ecological functional traits of reseeding or resprouting, respectively. The haplotype divergence of the ecotypes has also provided insights into the genetic history of these populations and highlighted the need for the establishment of appropriate conservation strategies for the protection of wild ecotypes.